34th International Conference on Efficiency, Cost, Optimization, Simulation and Environmental Impact of Energy Systems (ECOS 20 2022
DOI: 10.52202/062738-0011
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Rolling Horizon for operational optimization of multi-energy systems

Abstract: Operational optimization problems of multi-energy systems have to be solved repeatedly, e.g., to react to changing energy prices. Thus, operational optimization problems should compute fast. The computation time of operational optimization problems is, therefore, often reduced by the Rolling-Horizon method. The Rolling-Horizon method decomposes the original optimization problem heuristically into smaller subproblems. Each subproblem optimizes only the next few time steps of the whole time series. While reducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Note that the normalization variants lead to different ranges of values regarding the normalized solutions and, consequently, resulting δ -errors. To enable comparability between δ -errors calculated with different normalization variants, we use the relative δ -error δ rel introduced by Postels et al : 55 For each normalization variant, the δ -error is referenced to its maximum value that occurs if all but one, i.e. , 16 out of 17, objectives are omitted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the normalization variants lead to different ranges of values regarding the normalized solutions and, consequently, resulting δ -errors. To enable comparability between δ -errors calculated with different normalization variants, we use the relative δ -error δ rel introduced by Postels et al : 55 For each normalization variant, the δ -error is referenced to its maximum value that occurs if all but one, i.e. , 16 out of 17, objectives are omitted.…”
Section: Resultsmentioning
confidence: 99%
“…For energy system optimization, Postels et al analyzed the influence of normalization variants based on mathematical and environmental reference values on the identified key objective subset. 55 The authors show that, in their case study, mathematical normalization variants lead to similar results while the identified key objective subsets differed substantially for the environmental reference values.…”
Section: Methodsmentioning
confidence: 92%
“…An easy-to-implement approach to reduce computation time is the Rolling-Horizon method (Cao et al, 2019). For this reason, Rolling Horizon is often used in practice to reduce computation time (Bischi et al, 2017;Shin and Zavala, 2020;Kämper et al, 2021a) or to consider uncertainties (Gupta et al, 2016;Wang et al, 2015;Kopanos and Pistikopoulos, 2014). Rolling Horizon heuristically decomposes the original optimization problem into smaller subproblems along the time axis.…”
Section: Introductionmentioning
confidence: 99%
“…However, applying Rolling Horizon requires the selection of values for the parameters step size and foresight, which strongly influences the computation time and solution quality (Marquant et al, 2015). The https://doi.org/10.1016/j.compchemeng.2023.108208 Received 7 January 2023; Received in revised form 22 February 2023; Accepted 27 February 2023 following main trends occur (Kämper et al, 2021a): The larger the step size, the fewer subproblems to solve, but the longer the computation time of each subproblem. Thus, the choice of the step size results mainly in a trade-off in computation time.…”
Section: Introductionmentioning
confidence: 99%